An intraoral abscess incision model made from glove waste: an alternative preclinical learning aid for dentistry - Beti Indrawati; Tri Vina Winda Apriliana; Sri Pujiatun; Yosaphat Bayu Rosanto; Ivan Arie Wahyudi (Jurnal Teknosains, 2026)
Current developments require learning processes to become more dynamic and adaptive. Simulations based on realistic models are known to improve students’ manual skills as well as their confidence when dealing with real clinical cases. However, learning models that fully represent actual clinical conditions remain limited. The development of an intraoral abscess incision model using glove waste as a preclinical learning medium in dentistry offers an innovative approach, not only to reduce costs and medical waste, but also to support a more ecological and sustainable learning process. This study aimed to develop an abscess incision model based on glove waste as a preclinical learning medium in dentistry while supporting efficiency and medical waste reduction. The research method included the sterilization of glove waste, fabrication of a working model using dental stone, and preparation of an abscess substitute using glove waste filled with shampoo and covered with plasticine. Two types of models were developed, consisting of abscesses positioned in different locations and abscesses with variations in large and small sizes. The feasibility of the developed models was then evaluated through surveys that assessed functionality, reproducibility, and user perception, involving dental co-assistants and oral surgery residents who acted as supervisors during simulation sessions and questionnaires. The results indicated that the model was considered effective in improving understanding, knowledge, and skills, with excellent percentages of 70.81%, 62.50%, and 70.81%, respectively. The developed model was considered representative as an abscess incision model, although several improvements are still required. This study demonstrates that an abscess incision model made from glove waste is economical, environmentally friendly, effective, and representative as a learning aid for intraoral abscess incision procedures. The model also successfully improved practitioners’ understanding, knowledge, and skills, and was considered feasible as an alternative to commercially manufactured simulation tools.